قاضي تطبيق الجزاء تعزيز لسياسة النفعية العقابية (Journal of Academic Research, 2025)
The idea of this research has been put forward by the data of the failure that has become associated with the stage of penal implementation in its current form in the Libyan legislation and the confinement of legislative visions in the interior and stopping at the traditional pattern of leading the important stage in creating the balance between two rights of the social body that are contradictory in appearance, but consistent in their final content, namely its right to punish those who attack its interests. The other is its right to reform the condition of its accused sons and rid them of the filth of crime, which strongly imposes the extension of the supervision of the criminal judiciary to a stage following the issuance of the judicial ruling, so that the subject judiciary has the final say in creating the foundations of the desired balance, giving free rein to the punishment whenever it is beneficial, and replacing it whenever it becomes harmful and does not achieve its goal of reform and deterrence and loses its utility. This role, according to our vision, must be led by the subject judiciary through an institution with an independent administrative structure, headed by a judge who supervises the process of implementing the penalty in the form